Novel mutants of the aubergine gene. Issue 2 (2nd April 2016) - Sahin, H. Bahar; Karatas, Omer Faruk; Specchia, Valeria; Tommaso, Silvia Di; Diebold, Céline; Bozzetti, Maria Pia; Giangrande, Angela
ABSTRACT: Aubergine is an RNA-binding protein of the Piwi clade, functioning in germline in the piRNA pathway that silences transposons and repetitive sequences. Several mutations of this gene exist, but they mostly result in truncated proteins or correspond to mutations that also affect neighboring genes. We have generated complete aubergine knock-out mutants that do not disrupt the neighboring genes. These novel mutants are characterized by PCR and sequencing. Their nature is confirmed by female sterility and by the presence of crystals in testes, common to the aubergine loss of function mutations. These mutants provide novel and more appropriate tools for the study of the piRNA pathway that controls genome stability.